PENDAMPINGAN MANAJEMEN ORGANISASI DAN KEWIRAUSAHAAN PADA KELOMPOK DASA WISMA DI KECAMATAN DAU - Nuraini, Ida; Hadi, Syamsul (Jurnal Likhitaprajna, 2024)
The Dasa Wisma Bougenville 5B Mulyoagung Village group has been established for one year but until now there have been no activities because they do not have a work program. Even though Dasa Wisma has an important role in creating a prosperous family. For this reason, assistance is needed in managing this organization so that it can play a role in mobilizing its members so that the organization's goals can be realized. The aim of mentoring activities for Partners, namely the Dasa Wisma Bougenville 5B group, is, first, to help create organizational structures and work programs as well as practice implementing work programs. Second, entrepreneurship assistance in the form of establishing group or individual businesses. The implementation method is in the form of lectures, training and mentoring. The results of these activities were the formation of an organizational structure, work program and the formation of 4 Working Groups which immediately started their activities in the form of religious activities (learning tahsin, recitation and interpretation) every Saturday morning and training in corpse care. Entrepreneurship assistance in the form of education and entrepreneurial practice in producing dishwashing soap and marketing it. Environmental conservation activities include sorting and collecting plastic, electronic, glass, paper and cardboard waste to be sold together and the proceeds go to the organization's treasury. Dasa Wisma Bougenville 5B has been able to mobilize its members to be active in religious, entrepreneurial and environmental activities. Members who are active in Dasa Wisma activities are expected to increase their knowledge, organizational and entrepreneurial skills so that the goal of creating a prosperous family can be achieved.